PAPAIN ENZYME: A DIGESTIVE AID - PATEL, TINKAL (International Journal of Clinical and Biomedical Research, 2016)
Digestion is a process in which food is divided into forms that our body can use in performing various functions. It has large organic molecules like fat, carbohydrate, proteins.It then break doens into smaller parts like glucose, fatty acids and amino Acids. The human body has a complete digestion system from mouth to anus. Digestive enzymes are diverse and found in the saliva secreted by the salivary gland, in the stomach secreted by cells lining the stomach and in the pancreatic juice secreted by pancreatic exocrine cell. But, there is a presence of this much enzyme in the body and most of the people are facing the problem of indigestion and stomach pain due to the eating habits. Irregular timing of eating, fast food consumption and other reasons create the problem of indigestion.